Gagam-Palmultang Restores Immune Homeostasis and T Lymphocyte Activation in a Cyclophosphamide-Induced Immunosuppression Mouse Model - Jin Young Hong; Bo Ram Choi; Doo Ri Park; Jee Eun Yoon; Ji Yun Shin; Yoon Jae Lee; In-Hyuk Ha (Applied Sciences)
Gagam-palmultang (PMT), a traditional Korean herbal formula, has been used to treat various conditions; however, its immunomodulatory potential remains unclear. Our objective was to assess the immunomodulatory effects of PMT in an immunosuppression mouse model. In vitro, we assessed interleukin (IL)-10 production in concanavalin A (Con A)-stimulated mouse splenocytes using real-time polymerase chain reaction and enzyme-linked immunosorbent assays. In vivo, C57BL/6 mice were intraperitoneally administered cyclophosphamide (CPA) to induce immunosuppression, followed by the oral administration of PMT (100 or 200 mg/kg) once daily for 14 days to evaluate its effects on T lymphocyte activation and immune function restoration. Immune function was evaluated via flow cytometric analysis of CD4+ and CD8+ T cells, thymus index measurements, thymic histopathology, and hematological analysis of white blood cell, monocyte, lymphocyte, neutrophil, and eosinophil counts. PMT significantly increased IL-10 production in Con A-stimulated splenocytes. In immunosuppressed mice, PMT restored the thymus index, improved thymic histopathology, and enhanced hematological parameters. Flow cytometry showed a significant increase in CD3e+CD4+ and CD3e+CD8+ T lymphocytes, and histological evaluation revealed increased CD3+ lymphocytes in the thymus. These findings suggest that PMT enhances T lymphocyte activation and restores immune homeostasis under immunosuppressive conditions, demonstrating its potential as a herbal immunomodulatory agent.